2017
DOI: 10.1002/jlcr.3487
|View full text |Cite
|
Sign up to set email alerts
|

Fast indirect fluorine-18 labeling of protein/peptide using the useful 6-fluoronicotinic acid-2,3,5,6-tetrafluorophenyl prosthetic group: A method comparable to direct fluorination

Abstract: Fluorine-18 labeling of biomolecules are mostly performed by an indirect labeling method using a prosthetic group. Fluorine-18 labeled 6-fluoronicotinic acid-2,3,5,6-tetrafluorophenyl ester is a useful prosthetic group to radiolabel a protein. Recently we reported an improved preparation of this prosthetic group. To test the conjugation efficiency of the labeled ester prepared by this method we have performed conjugation reactions with two different peptides and a protein. Prostate-specific membrane antigen (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 66 publications
1
31
0
Order By: Relevance
“…We wanted to test the [ 18 F] fluoride elution efficiency using a quaternary ammonium triflate precursor (Scheme 1, 1) of benzaldehyde in different solvents with the intention to directly incorporate the fluoride in the product. Attempts to elute [ 18 F]fluoride from the Sep-Pak with 1 in acetonitrile were unsuccessful (Table 1) ammonium triflate precursor (2) in acetonitrile through the Sep-Pak containing [ 18 F]fluoride. Fluoride elution efficiency was tested using different conditions ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…We wanted to test the [ 18 F] fluoride elution efficiency using a quaternary ammonium triflate precursor (Scheme 1, 1) of benzaldehyde in different solvents with the intention to directly incorporate the fluoride in the product. Attempts to elute [ 18 F]fluoride from the Sep-Pak with 1 in acetonitrile were unsuccessful (Table 1) ammonium triflate precursor (2) in acetonitrile through the Sep-Pak containing [ 18 F]fluoride. Fluoride elution efficiency was tested using different conditions ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…38,[44][45][46] Although Olberg, Malik, and others have demonstrated the effectiveness of the [ 18 F]FPy-TFP prosthetic group for radiolabelling various peptides, intermediate purication of the [ 18 F]FPy-TFP was required prior to conjugation to a peptide in order to remove unreacted PyTFP-precursor that interferes with peptide radiolabeling. 38,[44][45][46] In addition, Olberg et al showed that hydrolysis of the PyTFP-precursor resulted in formation of 2,3,5,6-tetrauorophenyl-6-(2,3,5,6-tetrauorophenoxy)nicotinate (by-product (11)), which can hinder efficient radiolabeling of the peptide. 38 To facilitate purication, the ELIXYS FLEX/CHEM® radiosynthesizer can accommodate SPE-cartridges in multiple congurations, enabling intermediate cartridge based purications within the reaction sequence.…”
Section: Discussionmentioning
confidence: 99%
“…These yields are comparable to other automated 18 32 Radiolabeling of peptides with [ 18 F]FPy-TFP were previously performed manually using a variety of peptide coupling conditions. 38,[44][45][46] The original manual peptide radiolabeling with [ 18 F]FPy-TFP by Olberg et al utilized a 1 : 1 : 1 DMSO : MeCN : phosphate buffer (pH-9.0), 3-5 mg of peptide, and a reaction temperature of 40 C for 15 minutes to generate the [ 18 F]FPy-peptide in a 22.5 AE 6.0% yield (total synthesis time ¼ 85 minutes). 38 Malik et al manually radiolabeled a DUPApeptide (2 mg) with [ 18 F]FPy-TFP in 5 : 3 MeCN : H 2 O, containing 5.5 mg of sodium bicarbonate as a base, at 60 C for 10 minutes, resulting in a 48 AE 0.9% non-decay corrected yield (total synthesis time ¼ 50 minutes).…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that the [18 F]F-Py-TFP prosthetic group can be prepared in one step from the trimethylammonium precursor [46] and it has been utilized in the fluorine-18 labeling of albumin and c(RGDfK). [47] …”
Section: Indirect Methods For 18f-radiolabeling Of Biomoleculesmentioning
confidence: 99%